Taken [videorecording (DVD)] - Spielberg, Steven, 1946-; Holmes, Tina, 1973-; Gretsch, Joel, 1963-; Burton, Steve; Benz, Julie, 1972- (DreamWorks Home Entertainment, 2003)
Ten episodes from the television miniseries "Taken" presented by Steven Spielberg. An epic event spanning three families, four generations and 50 years of unearthly secrets. "Taken" launches into a realm of alien abductions and deadly conspiracies reaching from World War II to the present.